A COMPARISON OF THE PRODUCTION OF PI-O-MESONS IN PPBAR AND PP INTERACTIONS AT THE CERN ISR - Angelis, A; Basini, G; Besch, H; Breedon, R; Camilleri, L; Chapin, T; Cool, R; Cox, P; Vongagern, C; Grossopilcher, C; Hanna, D; Linnemann, J; et al. (1982)
A comparison of pp and pp interactions s=52.7 GeV at the CERN ISR. The quantities compared were the charged and neutral multiplicities, the total neutral transverse energy, Σ ET, up to 12 GeV, and the single π0 inclusive cross section up to pT = 5 GeV c. No significant differences were observed. © 1982.